Serviceability performance of composite cellular beams with partial shear connection. (November 2018) - Lawson, R.M.; Lam, D.; Aggelopoulos, E.; Hanus, F.
Abstract: For composite cellular beams, additional deflections occur due to the loss of bending and shear stiffness at the opening positions and also due to slip in the shear connectors caused by partial shear connection. Design formulae are presented for the additional deflection of composite beams with circular openings or for cellular beams as a function of the proportionate depth of the openings. The simplified formulae are calibrated against finite element results for both cellular and solid web beams and also against measured deflections of a 15.3 m composite cellular beam test. This additional deflection is presented as a function of flexural and shear terms that are a function of the span:depth ratio. For modelling of cellular beams to determine deflections, the circular opening may be represented by an equivalent rectangular opening of length equal to 70% of the opening diameter. Highlights: Simple formulae have been developed for the additional deflection of composite beams due to circular web openings. The method has been compared to results of a 15 m span cellular beam test Finite element modelling is used to calibrate a simple formula for the additional deflection due to the openings Finite element modelling included both symmetric and asymmetric cellular beam sections. The effect of flexible shear connectors is included in a formula for the effective stiffness of a composite cellular beam